2012
DOI: 10.1177/0194599812442867
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Biofilms from Tracheoesophageal Speech Valves Using a Novel Marine Microbial Deoxyribonuclease

Abstract: The nontoxic deoxyribonuclease NucB was effective in releasing more microorganisms from biofilms on tracheoesophageal speech valves. This reflects its potential ability to break up and disperse these biofilms. Future studies will aim to develop NucB as a novel agent to prolong the life span of tracheoesophageal speech valves, thus reducing health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In a special finding during an investigation into shifting films on seaweeds, the bacterial biofilms formed by a ubiquitous Bacillus licheniformis released an enzyme that allowed bacterial dispersal from the embedding medium of the biofilm. The NucB enzyme involved in this process is being developed to disrupt biofilms on the tooth surface after the successful disruption of the biofilms that cause sinusitis [119,120]. However, it remains to be seen whether this enzyme is generic and can effectively dislocate the biofilm structures secreted by other species.…”
Section: Biomedical Applications Of Marine Productsmentioning
confidence: 99%
“…In a special finding during an investigation into shifting films on seaweeds, the bacterial biofilms formed by a ubiquitous Bacillus licheniformis released an enzyme that allowed bacterial dispersal from the embedding medium of the biofilm. The NucB enzyme involved in this process is being developed to disrupt biofilms on the tooth surface after the successful disruption of the biofilms that cause sinusitis [119,120]. However, it remains to be seen whether this enzyme is generic and can effectively dislocate the biofilm structures secreted by other species.…”
Section: Biomedical Applications Of Marine Productsmentioning
confidence: 99%
“…Recently we reported a secreted bacterial nuclease, NucB, as an alternative novel biofilm dispersing enzyme. NucB was hypothesised to be released as an important enzyme for biofilm degradation and its mechanism of action on dispersing preformed biofilms is very effective (Nijland et al, 2010;Shakir et al, 2012). This could potentially be extended to breakup the ubiquitously present eDNA, leading to loosening of the EPS matrix and complete removal of majority biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…The marine environment and especially biofilm bacteria themselves have proven to be a rich source of antibiofilm compounds (Burgess et al 2003;Ortega-Morales et al 2008). Some of these compounds are involved in the detachment of biofilms, for example lipopeptides (Janek et al 2012), surfactins (Mireles et al 2001), glycolipids (Dusane et al 2011), whilst others can destabilise the biofilm matrix (Shakir et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces with different physical properties such as glass may promote a different biofilm composition from those examined in this investigation. Shakir et al (2012) have also suggested that techniques such as SEM may not be appropriate for the quantification of biofilms with any significant depth.…”
mentioning
confidence: 99%
See 1 more Smart Citation